Conductivity and phase morphology of carbon black-filled immiscible polymer blends under creep: an experimental and theoretical study. - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Schubert, Dirk W. (Physical Chemistry Chemical Physics, 2016)
Blends of carbon black (CB)-filled co-continuous immiscible polystyrene/poly(methyl-methacrylate) (PS/PMMA) with a PS/PMMA ratio of 50/50 and CB selectively located in the PS phase have been prepared by melt blending. The simultaneous evolution of conductivity and phase morphology of blend composites was investigated under shear and in the quiescent state at 200 °C. It was found that shear deformation had a significant influence on the conductivity of the unfilled PS/PMMA blend and its composites, which was attributed to the change of phase morphology during shear. After the shear stress of 10 kPa, the conductivity of PS/PMMA blends filled with 2 vol% of CB decreased by about two orders of magnitude and the phase morphology transformed from a fine co-continuous structure into a highly elongated lamellar structure. The deformation of phase morphology and the decrease of conductivity were weakened upon decreasing the shear stress or increasing the CB concentration. During subsequent recovery, pronounced phase structure coarsening was observed in the mixture and the conductivity increased as well. A simple model describing the behavior of conductivity under shear deformation was derived and utilized for the description of the experimental data. For the first time, the Burgers model was used to describe the conductivity, and the viscoelastic and viscoplastic parameters were deduced by fitting the conductivity under shear. The results obtained in this study provide a deeper insight into the evolution of phase structure in the conductive polymer blend composite induced by shear deformation.